Optimasi Sudut Baji, Kecepatan Pemakanan & Rpm Terhadap Kekasaran Permukaan Material SCM 440 Dengan Metode Respon Surface (RSM) - Saputra, Deri; Kurniawan, Zaldy; Husman, Husman (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
The development of manufacturing technology has developed so rapidly. In this study, SCM 440 steel material was used, which is an alloy steel of chromium molybdenum. This steel has the advantages of stable composition,low harmful elements,high steel purity. Surface roughness is important, surface roughness is defined as the irregularity of surface configuration in an object resulting from a finishing process. This study aims to determine the influence of process variables on the surface roughness rate of SCM 440 material by varying the total cutting angles of 700,750 and 800 then variations in feeding speed of 0.08mm, 0.09mm, and 0.10mm and spindle speed or RPM, namely 160,220, and 280 puts / min in the RSM method. The Rspon Surface method is a set of mathematical and statistical techniques that are useful for analyzing problems where several independent variables affect the response variable and determine the optimal value of the process variable. From the results of the study, the value of the Second order yˆ = + 0.092224 X1² + 0.208515 X2² - 0.03661 X3² was obtained. With stationary point value X0 = ( total Cut angle ) = - 0.382409, X0 = (feeding) = 0.161715, X0 = (RPM) = 0.578250. and found the optimal values of Wedge Angle (78.212), Feeding Speed (0.095 mm) and RPM (278.29 put/min). Then it can be analyzed the optimal value that is different from the value of the RSM method framework and if the values are the same then the research fails.